Effect of flue gas CO2 on the growth, carbohydrate and fatty acid composition of a green microalga Scenedesmus obliquus for biofuel production - Ji, Min-Kyu; Yun, Hyun-Shik; Hwang, Jae-Hoon; Salama, El-Sayed; Jeon, Byong-Hun; Choi, Jaeyoung (TAYLOR & FRANCIS LTD, 2017)
Effect of various flue gas CO2 concentrations (5%, 10% and 14.1%) on growth rate and biochemical properties of a green microalga Scenedesmus obliquus was investigated. S. obliquus showed the highest biomass production and growth rate (0.36 g L-1 and mu(max) = 1.00 day(-1)), total inorganic carbon removal (35.8 mg L-1), lipid productivity (9.9 mg L-1 day) and carbohydrate productivity (10.3 mg L-1 day) with 14.1% CO2 after 8 days of cultivation. Fatty acid methyl ester analysis revealed that the palmitic and oleic acid contents were increased up to 5% and 7% with 14.1% CO2, respectively. Application of flue gas CO2 enhanced the growth along with lipid and carbohydrate productivity of S. obliquus, which can be exploited for reducing the CO2 concentration.
Keywords: MUNICIPAL WASTE-WATER; LIPID PRODUCTION; BIOMASS PRODUCTION; CARBON-DIOXIDE; CHLORELLA-SOROKINIANA; BIODIESEL PRODUCTION; MIXOTROPHIC CULTURE; INORGANIC CARBON; LIGHT-INTENSITY; CNW-N